Curative measures identification in congestion management exploiting temporary admissible thermal loading of overhead lines. Issue 16 (28th May 2022) - Kollenda, Katharina; Schrief, Alexander; Biele, Charlotte; Lindner, Martin; Sundorf, Niklas; Hoffrichter, André; Roehder, Andreas; Moser, Albert; Rehtanz, Christian
Abstract: This paper demonstrates how to consider thermal reserves of overhead lines in optimization problems for congestion management with preventive (pre‐fault) and curative (post‐fault) actions effectively to ensure N‐1 security. Solving congestions curatively allows for higher base loadings and reduced congestion management volumes. At the same time, assets are exposed to higher risks of damage. The two proposed methods incorporate precise permanent and temporary admissible loading constraints for base and contingency situations already at the operational planning stage. The methods ensure that conductor temperatures stay below the assets' thermal limits at all times. The benefits of exploiting thermal reserves are analyzed in a case study to the future German transmission grid of 2030.